THE SCIENTIFIC WORK ON LANDSCAPE ANALYSIS IN BRAZIL: PERSPECTIVES FOR AN INTEGRATING DEBATE - das Neves, Carlos Eduardo; Salinas, Eduardo; Passos, Messias Modesto dos; Sanches Ross, Jurandyr Luciano; Cunha, Lucio (Univ Estado Rio Janeiro, 2021)
Introduction: The academic discussion on landscape expresses one of the most significant theoretical-methodological entry point of geography towards an integrating debate between society and nature. Besides, this approach has been used as an alternative to sectorial planning, which has displaced nature from cultures, deflating the current understanding of problems related to environmental degradation, and fragmentation and transformation of landscape. Objective: In this context, the present study aims to: (1) understand the geographic academic work in Brazil by examining scientific publications about the concept of landscape, between 2006 and 2016; and (2) briefly analyze the structure and dynamics of the national landscape complex. Methods: To that end, bibliometric research was carried out using scientific journals on Brazilian Geography by spotting different variables and seeking to understand the current state of research and the perspectives and tendencies in those scientific publications. Later on, based on Ross's, 2006, proposal about natural systems of (little and strongly transformed) landscapes, a discussion was held about the state of such Brazilian landscape mosaics. Results: At first, the study revealed a tendency towards the use of an integrative approach that relates landscape, local scale, river basins and environmental themes. Subsequently, the study identified four little-transformed natural landscapes and nine strongly transformed ones, which points to the heritage of old and recent processes of liaison between society and nature. Conclusion: It is hoped that the present discussion will serve as a basis for future research on the topic, not only from a theoretical perspective but also, and especially, from an applied perspective geared to territorial planning.
Keywords: Integrated Physical Geography; Landscape; Environment; Bibliometrics; Brazil